When Adat Laws and Shariah Islam Became Frogs in the Well: Critical Response to UU Pemerintahan Aceh, and Aceh’s Qanun for Tanah Ulayat in Aceh Singkil - Zulfikar RH Pohan (State of Islamic Institute Langsa, 2020)
Aceh as an autonomous region has adat laws and local people’s rights stipulated in the Aceh Provincial Law 2006, Aceh’s Qanun Law, and the Founding Principles of the Majelis Adat Aceh (Aceh Adat Assembly). On the other hand, the Constitution recognizes adat law in the amendment of the UUD 1945 of 2000 article 18b paragraph 2 by saying that customary land is a right for the community and the obligation for the state to protect indigenous peoples. However, ulayat land conflicts through regulations at the national and regional levels do not meet the same agreement in the settlement of ulayat agrarian conflicts. Other laws on Agrarian affairs, as well as the land and forestry sector also have overlapping definitions of ulayat land. This study provides an understanding of the dynamics and contestation between adat and religions in the midst of agrarian conflict. The main point observed in the journal is the annexation of land, the use of post-colonial theory to explain the aspect of deindigenization, which eliminates the soil as the basis of the adat. The study of agrarian conflict is not only based on the law but also concerns how the concept of land in indigenous culture is structurally distorted. This study is based on observations on the agrarian conflict in Aceh Singkil’s ulayat land in 2011. This article was compiled based on a qualitative normative-empiric method with a case study approach, the data in this study were obtained from time media observations and interviews of several community leaders in the ulayat land protester group with The HGU area of PT Nafasindo. This research resulted in the findings that the weakness of adat law and Islamic law in agrarian conflict is caused by the duality of the law and hegemonic of the colonial law in terms of setting the material base of indigenous communities.